Similarities and Differences between Indonesian and English Syntax: Implications for Teaching English Syntax to Students - Fitria, Tira Nur (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2025)
This research describes the syntactical comparison between Indonesian and English, both the similarities and differences, as well as the implications for language teaching and learning. This research uses contrastive analysis. The result analysis shows that the syntactic similarities between Indonesian and English cover various fundamental aspects of sentence structure and grammar, including word order, modifiers, auxiliary verbs, prepositional phrases, conjunctions, possession, relative clauses, and tense/aspect expression. However, syntactic differences exist, such as Indonesian's flexibility in word order, verb inflection, pronoun usage, lack of articles, different use of demonstratives, and distinct question formation methods. Understanding these differences is crucial for effective communication in both languages. For teachers, teaching English syntax involves steps like introducing word types, basic sentence structure, phrases/clauses, tenses, and connecting words, while considering both similarities and differences between the languages to facilitate learning. Understanding these similarities and differences between Indonesian and English is vital for teaching English to Indonesian students. First, highlighting shared concepts like subject-verb agreement and basic sentence structure establishes a comprehension foundation. Second, addressing differences prevents interference from the native language and promotes accurate English construction. Third, encouraging comparative analysis deepens understanding of both languages. Fourth, contextualized learning with relatable examples enhances comprehension. Fifth, explicit instruction on English syntax, especially differing aspects, is crucial. Sixth, error correction facilitates accurate English usage. Seventh, multisensory approaches reinforce understanding. Eighth, cultural sensitivity cultivates a respectful learning environment. These strategies empower instructors to effectively teach English syntax to Indonesian students. This research can add insights into the differences and similarities in the syntax of the two languages, as well as provide practical guidance for teachers in designing effective curricula and teaching strategies for English language learning for Indonesian-speaking students.